Platelet activation by charged ligands and nanoparticles: platelet glycoprotein receptors as pattern recognition receptors. (17th November 2021) - Montague, Samantha J.; Patel, Pushpa; Martin, Eleyna M.; Slater, Alexandre; Quintanilla, Lourdes Garcia; Perrella, Gina; Kardeby, Caroline; Nagy, Magdolna; Mezzano, Diego; Mendes, Paula M.; Watson, Steve P.
Abstract: Charge interactions play a critical role in the activation of the innate immune system by damage- and pathogen-associated molecular pattern receptors. The ability of these receptors to recognize a wide spectrum of ligands through a common mechanism is critical in host defense. In this article, we argue that platelet glycoprotein receptors that signal through conserved tyrosine-based motifs function as pattern recognition receptors (PRRs) for charged endogenous and exogenous ligands, including sulfated polysaccharides, charged proteins and nanoparticles. This is exemplified by GPVI, CLEC-2 and PEAR1 which are activated by a wide spectrum of endogenous and exogenous ligands, including diesel exhaust particles, sulfated polysaccharides and charged surfaces. We propose that this mechanism has evolved to drive rapid activation of platelets at sites of injury, but that under some conditions it can drive occlusive thrombosis, for example, when blood comes into contact with infectious agents or toxins. In this Opinion Article, we discuss mechanisms behind charge-mediated platelet activation and opportunities for designing nanoparticles and related agents such as dendrimers as novel antithrombotics.